KEARIFAN BUDAYA LOKAL MASYARAKAT MARITIM UNTUK UPAYA MITIGASI BENCANA DI SUMATERA BARAT - Lucky Zamzami; Hendrawati . (Universitas Andalas, 2014)
Local wisdom that exists in the community is potentially a very valuable in dealing with the problems of natural disasters that hit the region. Understanding of the potential of local wisdom in dealing with the threat of natural disasters is important in disaster mitigation efforts in disaster-prone areas. One of the natural disaster-prone areas in West Sumatra that have the potential of local cultural wisdom is Ulakan Nagari, Kec. Ulakan Tapakis, Kab. Padang Pariaman. This region includes the areas worst affected by the earthquake last 30 September 2009. However, these communities do not get a lot of casualties caused by the earthquake The power of religion as a major potential cultural wisdom of this community, namely the existence of the tomb of the great scholar Shaykh Burhanuddin considered believed society could reject any disaster so that when disaster strikes, the community has a great power to anticipate the disaster. The community did with various religious traditions, such as dhikr (prayer) in the tomb and on the waterfront and implement indigenous tradition (sort of ceremony Tabuik) as a sign of gratitude to Allah SWT. Besides the religious aspect, the public trust with marine geography which has the power of a tsunami hazard barrier so that people believe that the tsunami would not harm them